2009
DOI: 10.1136/adc.2008.155028
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of subependymal pseudocysts and choroid plexus cysts on neonatal cerebral ultrasound: a meta-analysis

Abstract: Bilateral multiple subependymal pseudocysts or choroid plexus cysts suggest an underlying disease. Further investigations should be undertaken even if the patient is otherwise normal. Parents of well newborns with a single cyst should be reassured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
3
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 38 publications
(37 reference statements)
0
24
3
2
Order By: Relevance
“…In the present study, 3.7% (119/ 3186) of all examined neonates were found to have cystic lesions, which is similar to other reports (Table 1). 27 Of those cystic lesions found, we found that 31.1% (37/119) presented as bilateral intracranial cysts (Table 2). However, we did not find any abnormal neurodevelopmental record in the following 18e24 months after discharge.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the present study, 3.7% (119/ 3186) of all examined neonates were found to have cystic lesions, which is similar to other reports (Table 1). 27 Of those cystic lesions found, we found that 31.1% (37/119) presented as bilateral intracranial cysts (Table 2). However, we did not find any abnormal neurodevelopmental record in the following 18e24 months after discharge.…”
Section: Discussionmentioning
confidence: 94%
“…27 The presence of an isolated subependymal cyst or a choroid plexus cyst usually resolves after a variable period of time, 29 and no serious neurodevelopmental complications occur in most cases. 29 However, in the meta-analysis of Alvarez and colleagues, 27 they found that one in four to five infants with bilateral multiple subependymal cysts or choroid plexus cysts may have a congenital infection or genetic anomaly.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of SEPCs has increased with the use of routine cerebral ultrasound (CUS); however, to our knowledge, there is no algorithm in the literature guiding clinicians, who face this pathology. As suggested in a recent meta-analysis,16 we prospectively enrolled newborns with SEPCs for follow-up, described the population characteristics and assessed the neurodevelopment at 6, 18 and 46 months.…”
Section: Introductionmentioning
confidence: 99%
“…1315 Unilateral subependymal, pseudo-, and choroid plexus cysts were not included in “any lesions” and excluded from the analysis as incidental findings. 16 …”
Section: Methodsmentioning
confidence: 99%